Telaah Hubungan Tongkonan dan Lanskap Budaya Toraja: Analisis Sistem Aktivitas dan Ekspresi Sistem Setting - Ramma, Zwasty Paskahlia; Hayati, Arina; Cahyadini, Sarah (Jurnal Lanskap Indonesia, 2024)
Tongkonan, as vernacular architecture, cannot be dissociated from its cultural landscape. Tongkonan and its cultural landscape form a holistic entity that constitutes Toraja culture as a whole. However, most current research focuses solely on Tongkonan’s architectural and structural aspects. There are still few studies that explore Tongkonan’s vernacular architecture in connection with its cultural landscape, including its relationship to the culture of its people and its geographical context. This research is a desk study with the aim of formulating aspects related to further examining the relationship between Tongkonan as vernacular architecture and its cultural landscape based on theory of systems of activity and systems of setting. In addition, this paper contributes to fulfilling the 11th SDGs, covering four pillars -social, economic, ecology, and cultural. The method used is qualitative-descriptive with content analysis to analyze data obtained from the literature study. The analysis is supported by empirical studies in Kete' Kesu village in North Toraja Regency. The chosen location is an ancient village with a fairly complete cultural landscape and good accessibility. The findings show that the systems of activity for Toraja people in Tongkonan and its cultural landscape include domestic, religius, ecology and socio-economic activities. The systems of setting for Tongkonan and its cultural landscape encompass Tongkonan itself, alang, grazing area, puya, rante, saroan, paddy field, forest/kombong, farm, lantang, middle yard, Tongkonan surrounding, penanian, territory/liliq, area diamben, area ma'dika, area renge direnge, bridge, villages, settlement, pasar, graveyard, parampa.